2007
DOI: 10.1016/j.cell.2007.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Stimuli Induce IKKα-Mediated Phosphorylation of PIAS1 to Restrict Inflammation and Immunity

Abstract: How inflammatory stimuli signal to the nucleus to restrict inflammation is poorly understood. Protein inhibitor of activated STAT1 (PIAS1), a transcriptional regulator that possesses small ubiquitin-related modifier (SUMO) E3 ligase activity, inhibits immune responses by selectively blocking the binding of NF-kappaB and STAT1 to gene promoters. We report here that PIAS1 becomes rapidly phosphorylated on Ser90 residue in response to various inflammatory stimuli. Mutational studies indicate that Ser90 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
139
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 26 publications
6
139
1
Order By: Relevance
“…NF-κB plays an important role in a wide spectrum of cellular responses and needs to be regulated properly at multilevels; inappropriate regulation of NF-κB is involved in a number of human diseases. Besides the well-characterized feedback pathway whereby newly synthesized IκB-α serves to shut off the signal [28], recent studies have gradually revealed a series of molecules, including A20 [29,30], CYLD [31,32], Twist [33], β-arrestins [34,35] and PIAS [36,37], all of which are capable of regulating NF-κB activity negatively. Here our work revealed that Dvl protein also serves as a negative regulator of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB plays an important role in a wide spectrum of cellular responses and needs to be regulated properly at multilevels; inappropriate regulation of NF-κB is involved in a number of human diseases. Besides the well-characterized feedback pathway whereby newly synthesized IκB-α serves to shut off the signal [28], recent studies have gradually revealed a series of molecules, including A20 [29,30], CYLD [31,32], Twist [33], β-arrestins [34,35] and PIAS [36,37], all of which are capable of regulating NF-κB activity negatively. Here our work revealed that Dvl protein also serves as a negative regulator of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] We also found that IKKa expression levels were higher in skin papillomas, a benign form of skin tumors, compared with normal skin in C57BL6 mice. 24 Approximately, only 3-5% of the papillomas progress to malignant carcinomas, but the rest eventually regress in C57BL6 mice.…”
mentioning
confidence: 61%
“…S5) indicating that PRMT1 does not control the sumoylation activity of PIAS1. Moreover, overexpression of the sumoylation-deficient PIAS1 mutant W372A (Liu et al 2007) revealed a similar repressive effect on the IFN induction of the same STAT1 target genes as wild-type PIAS1 (Supplemental Fig. S6).…”
Section: R E T R a C T E Dmentioning
confidence: 92%
“…Similar to the regulation of PIAS1 by PRMT1, S90 phosphorylation was needed to allow promoter recruitment of PIAS1 in NF-kB-activated transcription and resulted in the detachment of NF-kB from its targets. In contrast to the regulation by PRMT1, the Sumo E3-ligase activity was necessary for the repressive function of PIAS1, since a sumoylation-deficient PIAS1 mutant was defective in S90 phosphorylation (Liu et al 2007). Interestingly, we did not find phosphorylated PIAS1 species in response to IFNg treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation